PERANCANGAN & ANALISIS STATIK SISTEM TRANSMISI PADA MESIN BALL MILL DENGAN BANTUAN SOFTWARE - Agung Dwi Sapto (Asosiasi Dosen Muda Indonesia, 2024)
Shaft, pillow block, and pulley are one of the components in a ball mill machine. Where these components play a role in transmitting the rotation from the motor to the ball mill drum connected to it. This study aims to see the simulation and analysis on the assembly of shaft parts, pillow blocks, and pulleys which provide realistic force direction, model, and load performance. The shaft, pillow block, and pulley will perform static testing by inputting the load value into the Solidworks software. From the calculation of loading, the force value is 367.89 N, centrifugal force is 70 Rpm, and torque is 122.81 N.m. From the simulation results, the maximum von mises stress that occurs is 15,772.108 N / mm2. And the lowest safety factor that is obtained is 0.009. So that the shaft, pillow block, and pulley can be categorized as safe to use.